CONSUMER SEGMENTS AND VALUE PREFERENCES FOR TOMATOES IN PAKISTAN - H. Badar; A. Rasool; M. Boye (Journal of Animal and Plant Sciences, 2020)
The study identified value preferences of consumers at aggregate and segment level for suggesting upgrading measures to public and private stakeholders in tomato value chains in Pakistan. To this end, a consumer survey was conducted in three cities – Karachi, Lahore and Faisalabad. Using an interview schedule, data were collected through personal interviews of 275 tomato consumers at different retail outlets of vegetables. Results of the study revealed differences in consumption and purchase preferences of tomato consumers. Based on preferences for tomato quality attributes, hierarchical cluster analysis identified three segments labelled as rational, value seekers and indifferent consumers. While rational consumers preferred few basic quality attributes, the value seekers considered most of the quality attributes important in their purchase decisions. Indifferent consumers were concerned with merely using tomato as an essential ingredient for meal preparation. The study suggested that higher consumer value and returns can be captured through consumer driven improvements in production and marketing practices and collaboration and information sharing among chain participants. Relevant public sector institutions are also required to incorporate consumer requirements in their policies and actions plans for the development of tomato value chains in Pakistan.
Keywords: Value preferences; Consumer segments; Tomatoes; Cluster analysis; Value chains